PERBANDINGAN AKTIVITAS DAN HASIL BELAJAR GEOGRAFI MENGGUNAKAN ARTIKULASI DAN TPS KELAS X - Yusmala Adinta; Zulkarnain Zulkarnain; Sugeng Widodo (JPG (Jurnal Penelitian Geografi), 2013)
The aims of this research were to find out the differences in students’geography’s activity and outcomes with high and low initial ability of students who were taught through Articulation and Think Pair Share techniques in X grade MA Diniyyah Putri Lampung. This study used experimental method by Quasi-Experimental Design. The population was students of 1K grade. Number of samples is 42 students,taken by purposive sampling technique. Data collection used the students’ activities observation sheet and test techniques.Based on the hypothesis test, it was found that there was no significant difference on: 1)mean score of geography’s learning activities as a whole; 2) mean score of geography’s learning outcomes as a whole; 3) geography’s learning activity of high initial ability between students who were taught through Articulation and Think Pair Share; 4) geography’s learning activity of low initial ability between students who were taught through Articulation and Think Pair Share; 5) mean score of geography’s learning outcomes of high initial ability between students who were taught through Articulation and Think Pair Share; 6) mean score of geography’s learning outcomes of low initial ability between students who were taught through Articulation and Think Pair Share.Keyword: model, technique, articulation, think pair share